Linguistic and non-linguistic factors in defining some variable grammatical constructions in Mongolian - B., Möngönceceg (Acta Mongolica, 2018)
In this paper, the author aims to explain regularities and linguistic and non-linguistic factors in defining differences in meaning manifested by the same grammatical relations, based on three types of evidence: 1. Examples of constructions consisting of dative, locative and instrumental cases. 2. Examples of constructions containing causative voice. 3. Examples of constructions using a derivational suffix to create a noun. The description of sentence meaning and subject and object depend on whether the subject and object are Person-Person, Person-Animal, Person-Thing, Animal- Animal, Animal-Thing, Thing-Thing. Though the means of expression obey grammatical structures, it can be concluded that differences in meaning may be restricted by non-linguistic matters. This is crucial to defining detailed differences in the meaning and function of suffixes indicating grammatical relations, equivalent sentence components, and structures. In particular, from the viewpoint of grammatical structure, exemplified sentences may be correct in form but semantically inappropriate due to non-linguistic factors.